Determining the Most Suitable Costal Cartilage Level for Rhinoplasty: An Experimental Study - Alkan, Zeynep; Acioglu, Engin; Yigit, Ozgur; Bekem, Aylin; Azizli, Elad; Unal, Ahmet; Sahin, Feyzi (SAGE PUBLICATIONS LTD, 2012)
Objective. The aim of this study was to compare the biomechanical properties of septal cartilage (SC) and costal cartilage (CC) grafts harvested from different ribs and to find at which level CC has characteristics closest to SC. Study Design. Experimental cadaver study. Setting. Istanbul Training and Research Hospital. Material and Method. Cartilage grafts were harvested from the 6th, 7th, and 8th ribs and the SC of 10 fresh cadavers. Shaped cartilage grafts were subjected to a bending test. Results were measured, and the force-deflection curve was plotted. Flexural strength (sigma(f)) and flexural modulus of elasticity (E-f) were determined. Fractured surfaces were evaluated by scanning electron microscopy (SEM). Results. According to F-max, it was determined that ribs 6, 7, and 8 have significantly more durability compared with the SC (Ps = .030, .004, and .001). With regard to deflection, there was no significant difference between the SC and the 6th and 7th ribs and between the 6th and 7th ribs (Ps = 1.000, .088, and .306), while a significant difference was found between the SC and the 8th rib (P = .001). According to sf, no differences were seen between the 6th and 7th rib (P = .782), while difference was detected between the 6th and 8th and the 7th and 8th ribs (p = .001). Similar trends were established in E-f values as in sigma(f). These results were confirmed by SEM images. Conclusion. The 7th CC can be used as autograft because it shows similar properties to SC. However, the 6th CC is preferred if more flexibility is desired, and the 8th CC is preferred where more strength is needed.
Keywords: costal cartilage; septal cartilage; biomechanics; bending test; NASAL AUGMENTATION; GRAFT; RIBS; Otorhinolaryngology; Surgery